Assisted suicide and new issues: the Ethics Committees - Ciliberti, Rosagemma; Bonsignore, Alessandro; Gianatti, Paolo; Patroniti, Nicolò (Medicina Historica, 2023)
The recent reform of the organization of Ethics Committees in Italy is linked with the complex issue of end-of-life decisions. Starting from a reconstruction of the history and purpose of Ethics Committees, the article aims to provide an overview of the legislation and its evolution, and to highlight some questions that have not yet been fully answered in relation to assisted suicide. The confrontation with the dimension of suffering and pain represents one of the most problematic and still unresolved moral issues of the health and care professions. In this context, the creation of an Ethical Space, as an expression of a “medicine of proximity ", can be a valuable tool not only to find difficult answers to situations of severe suffering, but also to offer a comprehensive and supportive accompaniment to the person who asks to leave life, as well a concrete support to the health professionals involved in procedures to end-of-life, testifying a broad and active solidarity.